Phenolic Fractions from Dandelion Leaves and Petals as Modulators of the Antioxidant Status and Lipid Profile in an In Vivo Study - Michał Majewski; Bernadetta Lis; Jerzy Juśkiewicz; Katarzyna Ognik; Małgorzata Borkowska-Sztachańska; Dariusz Jedrejek; Anna Stochmal; Beata Olas (MDPI AG, 2020)
Alcoholic leaf and petal fractions of Taraxacum officinale (dandelion) were previously demonstrated to exert in vitro antioxidant and antithrombotic activities in blood plasma and platelets. Eight-week-old male Wistar rats (n = 6) were supplemented for four weeks with dandelion fractions (694 mg/kg of diet = 11.9 ± 0.6 mg daily). Dandelion leaf and petal fractions, which delivered daily 4.10 ± 0.05 and 1.41 ± 0.07 mg l-chicoric acid, respectively, were shown to exert antioxidative actions, measured as decreased levels of thiobarbituric acid-reactive substances (TBARS) in the spleen (≈0.8-fold, leaves and petals), brain (0.53-fold, leaves) and thoracic arteries (0.59-fold, petals). Moreover, petal fraction increased thiols in the blood plasma (1.58-fold), while leaf fraction decreased protein carbonylation levels (0.59-fold). Additionally, dandelion leaf fractions modified the lipid profile: decreased triglyceride (0.44-fold), total cholesterol (0.73-fold), lipoprotein combine index (0.32-fold) and the atherogenic index of plasma (0.62-fold). Dandelion fractions showed a beneficial decrease effect in the participation of cyclooxygenase products in the noradrenaline-induced vascular contractions of thoracic arteries. Meanwhile, only the dandelion leaf fraction augmented acetylcholine-induced vasodilation and upregulated KATP channels. The heart rate and blood pressure were not modified. Dandelion leaf and petal phenolic fractions, enriched with l-chicoric acid, are promising plant materials that may exert in vivo beneficial antioxidant effects.